PENGARUH KEPADATAN TANAH TERHADAP LAJU INFILTRASI PADA DAERAH PERMUKIMAN DI KECAMATAN ULAK KARANG SELATAN KOTA PADANG - Ahmad Farhan Lubis; widya Prarikeslan (JURNAL BUANA, 2026)
The city of Padang with rainfall of 4,200 mm per year, with a topography of rough relief with a height of 0.5 to 1,800 m above sea level, has long been a regular (annual) flood, while serious flood disasters occurred several times, namely in 1972, 1979, 1980, 1981, 1982, 1986, 2000, and 2004 with the impact of various sufferings experienced by the citizens of the city. From the results of data analysis, the average value of the infiltration rate in the South Ulak Karang catchment area is 0.015367 (cm/minute). Based on the classification table, the very low absorption area is Zone E < 0.1. Thus the tests that have been carried out in this area are very low. Infiltration is strongly influenced by the availability of green open land as a catchment area and water reservoir. Rainwater that is stagnant above the ground surface infiltrates into the soil, which causes a layer below the soil surface to become dry. saturated with water. The less green open land that functions to drain water into the soil, the smaller the infiltration rate will be.